Teen Titans. The complete first season [videorecording (DVD)] (DC Comics kids collection., 2006)
With awesome super skills and powers galore, these crimefighting partners kick butt and squash evil like nobody else. At roommates in Titans Tower, it's every hero for himself when it comes to living in peace. Not even super heroes can settle fights over who's in control of the TV remote.